1986
DOI: 10.1093/nar/14.20.8189
|View full text |Cite
|
Sign up to set email alerts
|

Replication origins are attached to the nuclear skeleton

Abstract: DNA fragments containing replication origins (oriDNA) were isolated from a chicken erythroblast cell line by a modified procedure of Zannis-Hadjopoulos et al. and studied in the renaturation reaction driven by either total or nuclear matrix DNA (nmDNA) from the same cells or from mature erythrocytes. We found that the unique sequences of nmDNA from erythroblasts (5 kb long) represented a specific subset of sequences constituting about a quarter of total DNA unique sequences, while the erythrocyte nmDNA 5 kb fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
76
0
2

Year Published

1990
1990
2001
2001

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 162 publications
(83 citation statements)
references
References 19 publications
5
76
0
2
Order By: Relevance
“…This would account for the three conclusions reached in the present study, namely (i) the correlation between SAR and ARS activities, (ii) the high correlation between the SAR strength and the ability to act as ARS, and (iii) the conservation of binding to the scaffold from D. melanogaster to yeast. Also, this view agrees both with the numerous reports on the cross-species conservation of the binding sites for Drosophila SARs in mammalian, chick, and yeast nuclear scaffolds (3,12,26,36,41) and with the fact that at least in two species, S. cerevisiae (3) and chicken cells (43), the association of genomic origins of replication with the scaffold has been clearly demonstrated. A second possibility is that the binding and the initiation of extrachromosomal replication might require distinct but contiguous sequences acting in concert.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…This would account for the three conclusions reached in the present study, namely (i) the correlation between SAR and ARS activities, (ii) the high correlation between the SAR strength and the ability to act as ARS, and (iii) the conservation of binding to the scaffold from D. melanogaster to yeast. Also, this view agrees both with the numerous reports on the cross-species conservation of the binding sites for Drosophila SARs in mammalian, chick, and yeast nuclear scaffolds (3,12,26,36,41) and with the fact that at least in two species, S. cerevisiae (3) and chicken cells (43), the association of genomic origins of replication with the scaffold has been clearly demonstrated. A second possibility is that the binding and the initiation of extrachromosomal replication might require distinct but contiguous sequences acting in concert.…”
Section: Discussionsupporting
confidence: 90%
“…The question of whether or not the ARSs identified in the present study are, at least in part, Drosophila replication origins is thus totally open. However, consistent with such a hypothesis are the facts that these ARSs are scaffold associated, as are replication origins (16,39,43,51), and that they are scattered over the 800-kb DNA molecule analyzed, as expected for replication origins (6). Two approaches can be taken to evaluate the SAR ability to promote replication in D. melanogaster.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…In the chicken alpha-globin gene domain (Razin et al, 1986), in the murine immunoglobulin locus (Cockerill, 1990), and in the lamin B2 locus (Lagarkova et al, 1998), the nuclear matrix attachment regions (MARs) were found to coincide with the replication origins. It is known that an altered chromatin structure is often present at the nuclear matrix attachment sites, and this may facilitate the binding and assembly of the replication complex by perturbing the nucleosomal organization of the chromatin (Benham et al, 1997).…”
Section: Dna Loop Domains and Organization Of Replicationmentioning
confidence: 99%
“…A higher level of DNA compaction, the DNA loop domains may also relate to spatial organization of DNA replication, as shown by co-localization of DNA loop anchorage sites with replication origins (Vogelstein et al, 1980;Smith et al, 1984;Razin et al, 1986;van der Velden et al, 1984). The DNA loop size also correlates with that of the replicons (BuongiornoNardelli et al, 1982;Marilley and Gassend-Bonnet, 1989).…”
Section: Introductionmentioning
confidence: 99%